Care managers' perceptions of eHomecare: a qualitative interview study. Issue 4 (4th July 2019) - Åkerlind, C.; Martin, L.; Gustafsson, C.
ABSTRACT: To implement information and communication technology (ICT) in elderly care can be a challenge for healthcare organisations. In Sweden, care managers (CMs) are responsible for offering ICT as a new part of homecare, i.e. eHomecare. The aim of this study was to focus on CMs' perspectives and describe their perceptions of eHomecare. The study has a qualitative approach. Semi-structured interviews based on vignettes were conducted with 12 CMs in a medium-sized municipality in central Sweden. Data were analysed using qualitative analysis. The findings showed that CMs are influenced by surrounding organisations and relatives in their decision to grant eHomecare. There were also difficulties in CMs' management of eHomecare. Furthermore, eHomecare was perceived to improve the quality of everyday life for older. It is understood that the management of eHomecare is a challenging task for CMs and a complex mission. Interactions among CMs, relatives, care providers, and other factors as for example CMs' own attitudes have an impact on CMs' decisions.